Avaliação de nutricionistas vinculados ao Programa Nacional de Alimentação Escolar em Palmas- TO - Silva, Larissa Rafaela da (Universidade Federal do Tocantins, 2021)
The National School Feeding Program encompasses within the school environment the human right to adequatefood and food and nutritional security, providing universal care to students enrolled in the public basic education network. The program has the professional nutritionist as the responsible technician, who has mandatory duties such as menu preparation, nutritional monitoring, carrying out actions of food and nutrition education, preparation of annual work plan and other duties that must be fulfilled in order to ensure quality and adequatenutrition for the students. Given this, the present work aims to verify the performance of the attributions performed by the Nutritionists Technical Responsible of the National School Feeding Program acting in the Regional Board of Education in the city of Palmas-TO. This is a descriptive cross sectional study in which data collected through structured questionnaires were applied to the Nutritionists in charge of the Palmas-TO Regional Board of Education. The research results showed that thirty attributions of the nutritionist were evaluated, 83.3% mandatory and 16.7% complementary. It was concluded that the Rt´s meet more than 2/3 ofthe analyzed attributes and most of the mandatory items (64% ) provided for in the legislation governing the program.